1995
DOI: 10.1149/1.2048389
|View full text |Cite
|
Sign up to set email alerts
|

Electrocatalysis of Anodic Oxygen‐Transfer Reactions: The Electrochemical Incineration of Benzoquinone

Abstract: The electrochemical performance of several anode materials is compared for the electrochemical incineration of p-benzoquinone in acetate buffer media (pH 5). The chemical oxygen demand (COD) estimated for benzoquinone by titration with standard permanganate solution can be decreased to virtually zero by electrolysis at electrodes comprised of Fe(III)-doped ~-PbO2 films on Ti substrates. Carbon dioxide is a product of the electrochemical process; however, the possibility of other volatile products cannot be dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
68
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(70 citation statements)
references
References 6 publications
2
68
0
Order By: Relevance
“…111 In view of the high rates of oxidation of organics at some doped coatings, it is not surprising that the studies have been extended to the complete oxidation of organics and hence for the removal of TOC/COD from effluent mimics. [115][116][117][118] Johnson and coworkers 109,111,112,[114][115][116]119,120,124,127 have made detailed studies of the mechanisms for the enhancement of rates by doping. They regard oxidations at lead dioxide anodes as oxygen transfer reactions rather than electron transfer reactions and therefore stress the importance of the activation of water as adsorbed OH radicals as the key step in the oxidations.…”
Section: Doped Lead Dioxidementioning
confidence: 99%
“…111 In view of the high rates of oxidation of organics at some doped coatings, it is not surprising that the studies have been extended to the complete oxidation of organics and hence for the removal of TOC/COD from effluent mimics. [115][116][117][118] Johnson and coworkers 109,111,112,[114][115][116]119,120,124,127 have made detailed studies of the mechanisms for the enhancement of rates by doping. They regard oxidations at lead dioxide anodes as oxygen transfer reactions rather than electron transfer reactions and therefore stress the importance of the activation of water as adsorbed OH radicals as the key step in the oxidations.…”
Section: Doped Lead Dioxidementioning
confidence: 99%
“…The most useful direct electrochemical method is anodic oxidation (Kaba et al, 1990;Kotz et al, 1991;Stucki et al, 1991;Comninellis andPulgarin, 1991, 1993;Murphy et al, 1992;Comninellis and Nerini, 1995;Feng et al, 1995;Johnson et al, 1999;Gandini et al, 2000;Rodrigo et al, 2001;Rodgers and Bunce, 2001;Wu and Zhou, 2001) where organic compounds are essentially degraded by reaction with adsorbed hydroxyl radicals at the anode surface, which are generated from water oxidation:…”
Section: General Aspectsmentioning
confidence: 99%
“…Thus, although the traditional Pt anodes has been used for this purpose (Kaba et al, 1990;Kotz et al, 1991;Stucki et al, 1991;Comninellis andPulgarin, 1991, 1993;Murphy et al, 1992;Comninellis and Nerini, 1995), it are less efficient that the oxide-base electrodes such as PbO 2 (Kaba et al, 1990;Feng et al, 1995;Wu and Zhou, 2001), doped PbO 2 (Feng et al, 1995), doped SnO 2 Stucki et al, 1991;Comninellis andPulgarin, 1991, 1993;Johnson et al, 1999), IrO 2 (Comninellis and Nerini, 1995;Rodgers and Bunce, 2001) or more recently to the boron-doped diamond thin-layer anode, BDD (Gandini et al, 2000;Rodrigo et al, 2001). On the other hand, the indirect electrochemical methods involves the previous formation of oxidizing agents such as H 2 O 2 (Hsiao and Nobe, 1993;Do 1993Do , 1994Ponce de Leon and Pletcher, 1995;Brilla et al, 1996;Brillas et al, 1998;Alvarez-Gallegos and Pletcher, 1999;Harrington and Pletcher, 1999;Brillas et al, 2000;Oturan et al, 2000, Oturan, 2000Oturan et al, 2001):…”
Section: General Aspectsmentioning
confidence: 99%
“…Aromatic compounds such as phenol and p-benzoquinone have often been used in prior studies [19 Á/23]. However, the reaction mechanisms of these compounds is rather complex, involving consecutive and parallel reaction pathways, and therefore are not deemed appropriate for investigating the role of catalyst composition in organic electro-oxidation reactions [21,23]. Before and after the oxidation studies, equilibrium CVs (n B/n eq ) were recorded to confirm that the electrochemical properties of these films were not altered during these anodic oxidation studies.…”
Section: Oxidation Characteristics For Organic's Using Pt/ Wo X and Smentioning
confidence: 99%
“…(3) Á/(5). In an alternative reaction scheme, it has been suggested that pre-adsorption of organics on specific surface sites of the anode is a key factor responsible for increased efficiencies of the anodic oxidation process [21]. There is still some controversy about the oxidative removal of organic compounds using metal oxide anodes and clarification of the reaction mechanism is needed.…”
Section: 'Anodic' Oxidation Of Model Organicsmentioning
confidence: 99%